INVESTIGATING STUDENTS' EXPERIENCES IN IMPLEMENTING LISTEN-READ-DISCUSS (LRD) STRATEGY IN READING COMPREHENSION OF NARRATIVE TEXTS - Adean, Cut; Puspitaloka, Nina; Rahmawati, Maya (IKIP Siliwangi, 2024)
This study focuses on exploring students' experiences in implementing the Listen-Read-Discuss (LRD) strategy in reading comprehension of narrative texts. The primary objective is to investigate students' experiences in the implementation of LRD strategy in reading comprehension of narrative texts. A qualitative approach is employed in this study, specifically utilizing a case study design, to provide in-depth insights. Research methods included participatory observation, where the researcher actively engaged with students during learning LRD sessions and semi-structured interviews were conducted to gather detailed reflections and feedback from participants. The participants in this study were students from grade XI at a public high school in Karawang City. In this study, the researcher only took 6 samples of students who were selected to be interviewed using a combination of non-probability and purposive sampling techniques, to ensure the representation of various perspectives and experiences. The results highlight that students generally have a positive experience of implementing the LRD strategy. This strategy facilitates learning for students in their understanding of the text and fosters motivation to engage deeply in the reading comprehension learning process. However, the study also recognized certain limitations, particularly related to time constraints which may have impacted the depth of the research findings.